Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/anie.201500649
|View full text |Cite
|
Sign up to set email alerts
|

Doping Effects in Cluster‐Mediated Bond Activation

Abstract: Gas-phase investigations of judiciously doped oxide clusters permit to address fundamental challenges related to, for example, the low-temperature oxidation of CO or the selective conversion of hydrocarbons. Modifying the size and composition of a free cluster in a controlled way enables the modification of local charge effects and of spin states, and spectroscopic studies in combination with computational work help to identify the active site of a catalyst and to unravel mechanistic details. Also, the interpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
115
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 136 publications
(336 reference statements)
1
115
0
5
Order By: Relevance
“…In addition to clarifying mechanistic aspects of HAT by oxo species, systems are presented which indicate how the reactivity of cluster oxides can be 'tuned' by modifying the charge and spin states of a reacting system by judicious 'doping' of the clusters [71]. Further, these gas-phase studies permit to identify the active sites of a metal oxide, and the role of the support material can be disentangled from the active component in composite catalysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to clarifying mechanistic aspects of HAT by oxo species, systems are presented which indicate how the reactivity of cluster oxides can be 'tuned' by modifying the charge and spin states of a reacting system by judicious 'doping' of the clusters [71]. Further, these gas-phase studies permit to identify the active sites of a metal oxide, and the role of the support material can be disentangled from the active component in composite catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…The question, which will be discussed next, deals with 'doping' effects and it will be shown that the controlled modification of a cluster oxide affects dramatically the local charge and spin distribution of the active site (for a recent review on this topic, see Ref. [71]). …”
Section: Heteronuclear Oxide Clusters: On Questions About the Active mentioning
confidence: 99%
“…12 As shown computationally, intracomplex spin transfer in these systems is energetically rather disfavored, 8a,10c,13 and one may wonder how to alleviate the problem. One way to modify crucial properties, such as the spin density around a reaction center, is by judicious "doping", 14 •+ the spin is equally distributed over the two bridging oxygen atoms of the cluster, resulting in a barrier for HAT too high in energy to be accessible at ambient conditions. Thus, HAT is observed only with substrates that have a weaker C−H bond, e.g., propane or butane.…”
Section: Hydrogen-atom-transfer: Revisitedmentioning
confidence: 99%
“…[1] Die direkte Erzeugung von Methanol oder Formaldehyd durch C-O-Kupplung wurde in vielen Gasphasenstudien zur Methanaktivierung [2] erfolgreich realisiert. [1] Die direkte Erzeugung von Methanol oder Formaldehyd durch C-O-Kupplung wurde in vielen Gasphasenstudien zur Methanaktivierung [2] erfolgreich realisiert.…”
unclassified